2021
DOI: 10.1371/journal.ppat.1009799
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic analyses of T cells in chronic HCV-infected patients dominated by DAA-induced interferon signaling changes

Abstract: Chronic infection with HCV is manifested by dysregulation of innate immune responses and impaired T cell function at multiple levels. These changes may impact susceptibility to other infections, responsiveness to antiviral therapies, vaccine responsiveness, and development of complications such as hepatocellular carcinoma. Highly effective direct-acting antiviral (DAA) therapy has revolutionized the management of chronic HCV, with expected cure rates exceeding 95%. DAA treatment represents a unique opportunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…CAR‐T or T cell receptor (TCR)‐T] against HCC. Multi‐omics profiling 6 and signatures of single immune cells 7 , 8 , 9 , 10 , 11 of the HCC TME have greatly promoted understanding of the immune landscape of the complicated HCC TME, which will eventually facilitate the development of a novel immunotherapy protocol against HCC.…”
Section: Introductionmentioning
confidence: 99%
“…CAR‐T or T cell receptor (TCR)‐T] against HCC. Multi‐omics profiling 6 and signatures of single immune cells 7 , 8 , 9 , 10 , 11 of the HCC TME have greatly promoted understanding of the immune landscape of the complicated HCC TME, which will eventually facilitate the development of a novel immunotherapy protocol against HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the impact of viral infections and liver cancer on immune diversity and virus-specific immunity is a potential avenue for the application of single-cell technologies. 37 38 39 40 41 42 43 ScRNA-seq combined with serial sampling of the liver via fine-needle aspiration biopsies has been recently employed to longitudinally study hepatic immune diversity during the course of HBV infection. 36 Several studies in humans and mice have also employed transcriptional and epigenetic approaches to examine the cellular programs and effector functions of virus-specific CD8 + T-cells before and after viral antigen clearance.…”
Section: Microenvironmental Reprogramming In Chronic Liver Diseasementioning
confidence: 99%
“… 36 Several studies in humans and mice have also employed transcriptional and epigenetic approaches to examine the cellular programs and effector functions of virus-specific CD8 + T-cells before and after viral antigen clearance. 37 38 39 40 42 Furthermore, the impact of direct acting antiviral therapy for chronic HCV infection has been mapped transcriptionally, revealing treatment-induced alterations in innate immune and interferon signalling. 42 Yates and colleagues employed assay for transposase-accessible chromatin with sequencing (ATAC-seq) to examine the presence of exhausted HCV-specific T-cells during longitudinal follow-up of HCV treatment and found that virus-specific T-cell exhaustion was irreversible after treatment-induced clearance, a phenomenon labeled epigenetic scarring.…”
Section: Microenvironmental Reprogramming In Chronic Liver Diseasementioning
confidence: 99%
See 2 more Smart Citations